2012
DOI: 10.5539/jas.v4n7p148
|View full text |Cite
|
Sign up to set email alerts
|

By-Products as Protein Source for Lactating Grasscutters

Abstract: The potential of grasscutters (Thryonomys swinderianus temminck) as a source of animal protein can be exploited with better understanding of its nutrient requirement. An experiment was conducted to determine the protein requirement of lactating grasscutters fed agro-industrial by-products namely; wheat offal and soybean meal. Sixteen 13 months old lactating grasscutters, in groups of four, were randomly allotted to four treatment diets formulated to respectively supply 10, 14, 18 and 22% crude protein (CP). Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…Les compositions chimiques des Rations alimentaires expérimentales sont comparables aux valeurs trouvées dans la littérature. Les taux de protéine brute obtenus dans cette étude pour les Rations alimentaires expérimentales se situent dans l'intervalle 17,41 à 19,59% et sont similaires à ceux trouvés par Wogar et al (2012) et par Wogar et al (2013). De même, les teneurs de cendre brute obtenues pour les trois Rations alimentaires expérimentales sont comprises entre 8,99 et 9,69%.…”
Section: Valeurs Nutritives Des Rationsunclassified
“…Les compositions chimiques des Rations alimentaires expérimentales sont comparables aux valeurs trouvées dans la littérature. Les taux de protéine brute obtenus dans cette étude pour les Rations alimentaires expérimentales se situent dans l'intervalle 17,41 à 19,59% et sont similaires à ceux trouvés par Wogar et al (2012) et par Wogar et al (2013). De même, les teneurs de cendre brute obtenues pour les trois Rations alimentaires expérimentales sont comprises entre 8,99 et 9,69%.…”
Section: Valeurs Nutritives Des Rationsunclassified
“…Studies have been conducted for the feasibility of the use of cotton by-products in ruminant feeding, especially cottonseeds (Aferri, Leme, Silva, Putrino & Pereira, 2005;Stelzleni, Froetschel, & Pringle, 2013) cottonseed meal, (Pina et al, 2006) cottonseed hulls (Magalhães et al, 2005;Kazama et al, 2008) and cottonseed cake for dairy cows (Alves et al, 2010); and wheat offal and soybean meal to grasscutters (Wogar & Ayuk, 2012). However, differences in dry matter (DM) intake related to fat sources using cottonseed and its by-products were also observed (Cranston et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The grasscutter presents an efficient process for the production of cheap meat from the utilization of cheap and easily available feedstuffs. It has been reported that the productive activities of grasscutters are positively affected by feeding agro-industrial byproducts Wogar and Ayuk (2012) and various other sources of fibre feedstuffs (Wogar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%